Wood deterioration by fungi / Syed Azhar Syed Ab Aziz - Syed Ab Aziz, Syed Azhar (2006)
Wood is a biological material and subject to decay, insect, and marine borer attack. Fungi are the major biotic agents in wood deterioration. As the wood have the higher value and important to world economy, their damage directly gives the effects to the industry to become higher losses. However, when wood is used in a more or less permanent application, it must be protected from biological degradation. Treating wood with the appropriate preservative increases its service life, and also helps to conserve our nation's timber resources. Treated wood has long been used for products such as crossties and pilings, and many new applications that have been developed today. Wood preservation also should be upgraded and study to make sure the wood quality in secured and environment ecosystem will be protected.